FEATURES OF COLLAGEN METABOLISM IN PREMENOPAUSAL WOMEN WITH STRESS URINARY INCONTINENCE ON THE BACKGROUND OF CONSERVATIVE AND LASER TREATMENT - Anna Melnichenko; Maryna Puchko; Tetiana Kovaliuk; Igor Usevych (Bogomolets National Medical University, 2019)
The article summarizes the arguments and counterarguments in the scientific discussion on the influence of undifferentiated connective tissue dysplasia on the development of stress urinary incontinence in premenopausal women and approaches to the treatment of this pathology. The main purpose of the study is to determine the characteristics of collagen metabolism in premenopausal women with stress urinary incontinence in order to improve treatment tactics and develop a differentiated approach to the prevention of this pathology in the future. The systematization of these literature sources and the lack of a unified approach to the treatment of stress urinary incontinence in premenopausal women showed the need to find new approaches to the treatment of this disease, which will affect the etiopathogenetic links of stress urinary incontinence in this category of gynecological patients. The relevance of the study of this pathology is that stress urinary incontinence is a problem that significantly reduces the quality of life of women in premenopause, causes isolation and self-doubt, and in certain cases can lead to psychological disorders. The methodology of the study was a prospective clinical and statistical examination, which involved 133 patients with stress urinary incontinence. Depending on the prescribed therapy observed women were divided into two groups. The main group included 57 women with premenopausal stress incontinence, which obtained laser therapy in order to correct the manifestations of the disease. A comparison group was formed by 76 premenopausal patients with stress urinary incontinence who received conservative treatment. In all patients of the examined groups, except general clinical examination we determined markers of synthesis (Total P1NP, Total P3NP) and resorption (deoxypyridinoline Pyriliks - D) of connective tissue at the initial level, immediately after treatment and after 6 months of treatment, the duration of the study was ten months. The results of a clinical study of the content of markers of synthesis and resorption of connective tissue in premenopausal women with stress urinary incontinence, which showed that this category of patients on the background of laser therapy marked a significantly positive effect obtained as a result of treatment aimed at increasing the average level of the marker of collagen synthesis type I and reducing the average level of the marker of collagen synthesis type III, as well as normalization of the average level of the marker of connective tissue resorption. The study empirically confirms and theoretically proves that the use of laser therapy is pathogenetically, because its positive effect is realized by affecting the connective tissue of the genital diaphragm, stimulating the production of collagen and type and synergistically inhibiting the production of collagen type III and Pyriliks-D. Results of the study can be useful for gynecological hospitals, General practitioners and family medicine and doctors of antenatal clinics.